Determination of the location of sonic boom - MAKAREWICZ, Rufin (Archives of Acoustics, 1976)
In the paper the results of theoretical considerations which permit to determine the location of sonic boom of shock wave produced during supersonic flight are given. It has been assumed that the earth's atmosphere is a stratified medium in which the velocity of sound propagation as well as wind velocity are magnitudes which depend only on the height. For general case (at arbitrary manoeuvring of aircraft) a procedure algorithm has been defined which permits to predict the boundary of audibility area. It has also been proved that for certain types of manoeuvring (including also rectilinear flight), defined, by condition (9), this algorithm enables the determination of coordinates of audibility area (grazing points) (x_A, y_A) as well as (x_B, y_B) in the analytical form (10). In the case of still atmosphere the obtained results are simplified to a well-known relation (13) determining the width of audibility belt of a shock wave.